Obesity, Type 2 Diabetes and the Adipose Organ A Pictorial Atlas from Research to Clinical Applications - Cinti, Saverio (Springer International Publishing, 2018)
This richly illustrated book provides a detailed description of the gross anatomy, light microscopy, immunohistochemistry, and electron microscopy of the adipose organ, which comprises subcutaneous and visceral fat depots. Findings in mice of differing genetic backgrounds (obesity prone and resistant) and maintained in standard and various physiologic and pathologic conditions are presented. The latter conditions include chronic cold exposure, warm exposure, fasting, pregnancy-lactation, and obesity. Features of the fetal adipose organ are described in a separate chapter, and results from transgenic mice are also presented when relevant. The human adipose organ is addressed in several chapters that include magnetic resonance and fetal findings. Most of the results regarding the adipose organ anatomy in different physiologic conditions are new, and the story of pink adipocytes (white-to-pink transdifferentiation) is quite innovative. The concept of using browning of the adipose organ as a therapeutic tool for obesity must take into consideration the anatomic and morphologic aspects described here, and the study of pink adipocytes could lead to a better comprehension of breast cancer tumor biology. This book will be of interest to all scientists who deal with obesity and related disorders.